Validation of a Spanish version of the Foreign Language Classroom Anxiety Scale in Peruvian secondary education students - Quispe-Sanca, Ruth V.; Arteta-Sandoval, Gissel; Quispe-Sanca, David; Morales-García, Wilter C. (Frontiers in Education, 2024)
Background Anxiety in learning foreign languages is a global phenomenon that impacts students’ academic performance, with English being a critical language in secondary education. The Foreign Language Classroom Anxiety Scale (FLCAS) has been widely used to assess this anxiety. However, the need to validate and adapt the scale for specific cultural contexts remains a priority in educational research. Objective To assess the validity and reliability of a Spanish version of the FLCAS among a sample of Peruvian secondary education students, in order to better understand the structure of language learning anxiety in this context. Methods A total of 818 students from four public educational institutions in southern Peru participated. An instrumental design was used, which included descriptive analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and assessments of convergent, divergent validity, and measurement invariance by gender. Results The EFA recommended a four-factor model that explained 32% of the total variance. Subsequent CFA adjusted this model to 24 items with optimal fit indices (CFI = 0.969; RMSEA = 0.045). The reliability of the factors was acceptable (α > 0.70 for all factors). Convergent and divergent validity was confirmed through significant correlations with related constructs (Fear of Negative Evaluation and Enjoyment of Foreign Language). Gender invariance analysis indicated that the scale is equally applicable to men and women. Conclusion The Spanish version of the FLCAS is a valid and reliable tool for assessing foreign language classroom anxiety among Peruvian secondary education students. This study contributes to the field of language teaching by providing evidence of the cultural applicability of the FLCAS in the Peruvian context, thus facilitating more effective pedagogical interventions to address language learning anxiety.